A biomechanical analysis of the knee joint during power snatch - Zainuddin, Fara Liana (Universiti Sains Malaysia, 2015)
This study focuses on the biomechanics of the knee joint which is one of the most frequently injured joint among weightlifters. Most of the techniques in snatch event are associated to knee flexion especially during squatting phases. The purpose of the study was to compare the range of motion (ROM) of the knee joint and barbell acceleration during one Repetition Maximum (1RM) and 50% of 1RM power snatch, and evaluate the knee joint reaction force (JRF) during 50% of 1RM power snatch. 25 state-level weightlifters were recruited voluntarily for the study. Standard 1 RM power snatch test was analyzed using two-dimensional (2D) kinematic method. Next, the knee joint ROM, barbell acceleration and knee JRF for 50% of 1RM power snatch were analyzed using three-dimensional (3D) kinematic method. The demographic result showed that physical evaluation of the athletes was in fair category. The Paired t-test showed that there was a significant difference of the knee joint ROM between 50% and 1-RM power snatch. The barbell accelerated faster during acceleration 50% of 1RM power snatch compared to 1RM power snatch (P = 0.044) particularly during second pull phase. Lastly, descriptive statistics of the knee joint reaction force (JRF) of weightlifters during 50% of 1RM power snatch that normalized to the bodyweight were 0.33 ± 0.20 N.m/kg.m for male weightlifters and 0.75 ± 1.68N.m/kg.m for female weightlifters. Overall, the knee range of motion and barbell acceleration decreased as the load of the barbell increased. The knee JRF of weightlifters during 50% of 1RM power snatch was within the normal range of knee JRF during squatting.